1997
DOI: 10.1007/bf01728309
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of iodine-123 metaiodobenzylguanidine radioaerosol as a marker of pulmonary neuroadrenergic function

Abstract: Iodine-123 metaiodobenzylguanidine (123I-MIBG) radioaerosol is of potential use in the investigation of the neuroadrenergic function of the lungs; however, before the method can be successfully employed the following issues need to be clarified: (1) Does the nebulization affect the radiochemical purity of 123I-MIBG? (2) Is the pulmonary distribution of inhaled 123I-MIBG homogeneous in normal subjects? (3) Does the pulmonary clearance of inhaled 123I-MIBG reflect the functional status of the neuroadrenergic sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Damaged AECs cannot efficiently extract circulating 123 I-MIBG (9,12,13,28). The previous animal model studies of pulmonary vascular damage showed a linear relationship between the degree of reduced 123 I-MIBG uptake and loss of the pulmonary vascular bed (17,23). Poor delivery of 123 I-MIBG due to decreased perfusion also may reduce 123 I-MIBG uptake, as 123 I-MIBG defects were persistently seen at the lung lobes with perfusion defects in our patients.…”
Section: Rgbmentioning
confidence: 93%
See 2 more Smart Citations
“…Damaged AECs cannot efficiently extract circulating 123 I-MIBG (9,12,13,28). The previous animal model studies of pulmonary vascular damage showed a linear relationship between the degree of reduced 123 I-MIBG uptake and loss of the pulmonary vascular bed (17,23). Poor delivery of 123 I-MIBG due to decreased perfusion also may reduce 123 I-MIBG uptake, as 123 I-MIBG defects were persistently seen at the lung lobes with perfusion defects in our patients.…”
Section: Rgbmentioning
confidence: 93%
“…Although extracellular 123 I-MIBG increases because of decreased extraction of circulating 123 I-MIBG to damaged AECs and sympathetic neurons, decreased perfusion disrupts back-diffusion of this component to systemic circulation (15,17,21). Lack of integrity or dysfunction of AECs in PE patients also decreases the 123 I-MIBG washout rate, as various other lung disorders with injury of AECs persistently show a decreased 123 I-MIBG washout rate (16,18,(20)(21)(22)(23)34).…”
Section: Rgbmentioning
confidence: 99%
See 1 more Smart Citation
“…Noradrenergic dysfunction in bronchial innervation has been demonstrated in a group of patients with type 1 diabetes who underwent lung ventilation scintigraphy with 123-Imetaiodobenzylguanidine (MIBG) [40]. The radiotracer was taken up in the lung by the same mechanism that controls the uptake of norepinephrine and selectively binds bronchial neuroadrenergic receptors [78]. Diabetic patients with autonomic neuropathy showed an increased lung uptake of 123-MIBG and a decreased rate of its clearance [40].…”
Section: Bronchomotor Tone and Control Of Ventilationmentioning
confidence: 99%
“…By sharing several pathways with noradrenaline in the adrenergic nerve terminal and being non-metabolized, MIBG qualifies as a reliable marker of neuroadrenergic activity [19]. The scintigraphy was performed as previously reported [9].…”
Section: Neuroadrenergic Bronchial Innervationmentioning
confidence: 99%